Abandon the Dead Donor Rule or Change the Definition of Death? - Veatch, Robert M (Kennedy Institute of Ethics journal, 2004)
, Research by Siminoff and colleagues reveals that many lay people in Ohio classify legally living persons in irreversible coma or persistent vegetative state (PVS) as dead and that additional respondents, although classifying such patients as living, would be willing to procure organs from them. This paper analyzes possible implications of these findings for public policy. A majority would procure organs from those in irreversible coma or in PVS. Two strategies for legitimizing such procurement are suggested. One strategy would be to make exceptions to the dead donor rule permitting procurement from those in PVS or at least those who are in irreversible coma while continuing to classify them as living. Another strategy would be to further amend the definition of death to classify one or both groups as deceased, thus permitting procurement without violation of the dead donor rule. Permitting exceptions to the dead donor rule would require substantial changes in law—such as authorizing procuring surgeons to end the lives of patients by means of organ procurement—and would weaken societal prohibitions on killing. The paper suggests that it would be easier and less controversial to further amend the definition of death to classify those in irreversible coma and PVS as dead. Incorporation of a conscience clause to permit those whose religious or philosophical convictions support whole-brain or cardiac-based death pronouncement would avoid violating their beliefs while causing no more than minimal social problems. The paper questions whether those who would support an exception to the dead donor rule in these cases and those would support a further amendment to the definition of death could reach agreement to adopt a public policy permitting organ procurement of those in irreversible coma or PVS when proper consent is obtained.